Pre-breakup continental extension in East Gondwanaland and the early opening of the eastern Indian Ocean - Powell, C. McA; Roots, S. R.; Veevers, J. J. (Tectonophysics, 1988)
Extension of continental crust by up to 360 km on a north-northeast azimuth in the Great Australian Bight occurred prior to the Middle Cretaceous (96 Ma) onset of seafloor spreading between Australia and Antarctica. This large amount of continental extension is constrained to the Late Jurassic (≈ 160 Ma)-Middle Cretaceous interval, about a pole estimated to lie about 40° southeastward of southeastern Australia. Using bathymetric data combined with seismic and magnetic determinations of the continent-ocean boundaries off Australia, India and Antarctica, we determine a revised fit of East Gondwanaland prior to continental extension, and at various stages thereafter. In the first stage from 160 to 132.5 Ma (≈ M11), India-Australia rotated from Antarctica with continental crustal extension between Australia and Antarctica and largely transform motion between the Coromandel Coast margin of India and the Kron Prins Olav Kyst margin of Antarctica. In the second stage, from 132.5 to 96 Ma, India rotated northwestward away from Australia-Antarctica, producing M10 and younger magnetic anomalies along the western margin of Australia. Continental extension was greatest between Australia and Antarctica during this stage. The newly determined 132.5-96 Ma rotation between India and Australia provides an improved fit between the orientation of observed M10-M0 magnetic anomalies and the southward decrease in spreading rate off the western Australian margin. Together with bathymetry, the new rotation parameters lead to identification of the abandoned 96 Ma spreading ridge along the Lost Dutchmen and Dirck Hartog ridges. The Naturaliste Fracture Zone is found to lie nearly parallel to the Early Cretaceous transform direction between India and Antarctica suggesting that slow seafloor spreading, required between Australia and Antarctica to accommodate the continental extension further east, occurred between Naturaliste Fracture Zone and the M4-M0 anomalies adjacent to the Naturaliste Plateau. The revised fit of India in East ...